Literature Review: Diagnosis, Treatment, and Prevention of Refractive Disorders in Adolescents - Putri, Imey Pinasty Harianto (Jurnal Biologi Tropis, 2025)
Refractive disorders, including myopia, hyperopia, astigmatism, and presbyopia, often appear from childhood, especially adolescence, through to old age. These conditions significantly impact the quality of life, academic achievement, and psychosocial well-being of sufferers. This literature review outlines article analysis to determine how to prevent, detect, and treat refractive disorders in adolescents. The review method used systematic literature. The findings of the literature study indicate that refractive disorders are a major cause of visual impairment, especially in adolescents who are still growing. Refractive disorders can impact students' quality of life and academic achievement. Diagnosis is made by examining visual acuity using a Snellen chart or LogMAR, followed by a corrective lens test. Treatment of refractive disorders can include the use of glasses, contact lenses, and refractive surgery procedures such as LASIK. The increasing global prevalence of refractive disorders emphasizes the importance of prevention, early detection, and appropriate management to reduce blindness and improve quality of life. In conclusion, prevention, early detection, and treatment of refractive disorders in adolescents can be used to avoid or reduce these diseases.